Developing Scientific Approach-Based E-Module Assisted by Kvisoft Flipbook Maker Application for Grade X of Senior High School Students - Nurfajriyah; Suzanne, Nina (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
The limitations of the teaching materials, the fact that the students' characteristics are not reflected in the materials and the absence of sample questions, individual assignments, or evaluations of narrative text materials in class X English teacher's teaching materials are the issues covered in this study. The aims of this research are to: (1) describe the needs on teachers and students for an electronic module (e-module) based on the scientific approach; (2) develop prototype for e-module based on the scientific approach; and (3) describe the conclusion of experts’ validation of the e-module. R&D research was used in this study. The study was only done up until the develop step of the 4D development model, which has four stages: define, design, develop, and disseminate. Three validators—two lecturers and one teacher—conducted validity tests on the researchers’ development for this study in order to evaluate it. Based on the research, (1) narrative text e-module teaching materials employing a scientific approach are required for both teachers and students. (2) The e-module narrative text prototype adheres to the scientific approach. (3) The validation test on e-module narrative text for English learning is 76.89% with a valid category. This demonstrates that using the scientific approach-based e-module narrative text material that was developed with the help of Kvisoft flipbook maker is valid.